Laboratory evaluation of the compatibility of Beauveria bassiana with the egg parasitoid Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) for joint application against the oriental fruit moth Grapholita molesta (Lepidoptera: Tortricidae). Issue 8 (10th June 2022) - Wu, Yanan; Fang, Haibo; Liu, Xiaoxia; Michaud, J.P.; Xu, Haoyang; Zhao, Zhihua; Zhang, Songdou; Li, Zhen
Abstract: BACKGROUND: The entomopathogenic fungus Beauveria bassiana and the egg parasitoid Trichogramma dendrolimi can both contribute to biological control of the global fruit borer Grapholita molesta . To derive insights for optimizing their combined application in augmentation programs, we assayed fungal pathogenicity to both G. molesta (eggs, larvae and adults) and adult parasitoids, and assessed wasp acquisition and transmission of fungal spores following their emergence from B. bassiana ‐treated host eggs. RESULTS: Concentrations of 10 8 conidia mL −1 of B. bassiana and higher caused virtually complete mortality of G. molesta larvae, but less than 30% mortality of eggs, and female moths surviving treatments had reduced fecundity. More than 80% of adult T. dendrolimi survived B. bassiana treatments of 10 7 conidia mL −1, and more than 60% survived 10 9 conidia mL −1, with surviving females achieving reproductive success equivalent to controls . Parasitoid females preferred healthy eggs over B. bassiana ‐infected ones in choice tests; wasps emerging from treated eggs carried about 10 4 conidia each and contributed an additional 11% host mortality in trials combining both agents. CONCLUSION: Our results indicate that combined applications of B. bassiana and T. dendrolimi can have complimentary impacts on G. molesta, the wasps compensating for low fungal pathogenicity to eggs and their progeny potentially aiding in subsequent disease transmission. Although foraging wasps tended to avoid infected eggs, negative interactions between the two agents might be further mitigated by timing B. bassiana applications from late instar larva to early moth stage, and T. dendrolimi releases several days later to coincide with peak oviposition periods. © 2022 Society of Chemical Industry. Abstract : Schematic overview of the proposed strategy for compatible application of Beauveria bassiana and Trichogramma dendrolimi for management of Grapholita molesta population in fruit orchards based on laboratory bioassays.